2019
DOI: 10.1038/s41598-019-41763-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical Co-registration of MRI and On-scalp MEG

Abstract: To estimate the neural generators of magnetoencephalographic (MEG) signals, MEG data have to be co-registered with an anatomical image, typically an MR image. Optically-pumped magnetometers (OPMs) enable the construction of on-scalp MEG systems providing higher sensitivity and spatial resolution than conventional SQUID-based MEG systems. We present a co-registration method that can be applied to on-scalp MEG systems, regardless of the number of sensors. We apply a structured-light scanner to create a surface m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Another barrier for the development of a speech-BCI is that MEG is currently not suitable for this application due to its high cost, size, and immobility. Encouraging recent work on wearable, OPMbased MEG systems (Boto et al, 2018;Roberts et al, 2019;Zetter et al, 2019) has shown that it is possible to build portable MEG machines with a significantly reduced cost and size (equivalent to the size of a helmet). This technological advance opens the possibility for utilizing OPM-based MEG as a speech-BCI to potentially restore communication for locked-in patients.…”
Section: Toward a Next-generation Speech-bcimentioning
confidence: 99%
“…Another barrier for the development of a speech-BCI is that MEG is currently not suitable for this application due to its high cost, size, and immobility. Encouraging recent work on wearable, OPMbased MEG systems (Boto et al, 2018;Roberts et al, 2019;Zetter et al, 2019) has shown that it is possible to build portable MEG machines with a significantly reduced cost and size (equivalent to the size of a helmet). This technological advance opens the possibility for utilizing OPM-based MEG as a speech-BCI to potentially restore communication for locked-in patients.…”
Section: Toward a Next-generation Speech-bcimentioning
confidence: 99%
“…In order to enable source localisation, accurate knowledge of the sensor locations and orientations relative to the brain is required. This was provided by a 3-dimensional optical imaging system (structure IO camera (Occipital Inc., San Francisco, CA, USA) coupled to an Apple iPad, operating with Skanect Pro software) and an anatomical MRI scan Homölle and Oostenveld, 2019;Zetter et al, 2019). The anatomical MRI was recorded using a 3 T Philips Ingenia MRI system, running an MPRAGE sequence, at an isotropic spatial resolution of 1 mm.…”
Section: Opm Co-registrationmentioning
confidence: 99%
“…To fix the position of the subject's head inside the helmet, dummy sensors were inserted into sockets on the sides of the helmet so that they gently pressed on the head on each side. MEG-MRI coregistration was performed using an optical scanner as described by Zetter, Iivanainen, and Parkkonen (2019); an example of coregistered OPM positions with respect to the subject's head is shown in Figure 1.…”
Section: Meg Acquisitionmentioning
confidence: 99%